A pillar[5]arene-based covalent organic framework with pre-encoded selective host–guest recognition. Issue 40 (23rd September 2021) - Liu, Lu; Hu, Yiming; Huang, Shaofeng; Jin, Yinghua; Cui, Jingnan; Gong, Weitao; Zhang, Wei
Abstract : A novel pillar[5]arene-derived (P5 ) COF was rationally designed and synthesized, which exhibited superior performance in selective gas adsorption and paraquat binding. Abstract : It is highly desirable to maintain both permanent accessible pores and selective molecular recognition capability of macrocyclic cavitands in the solid state. Integration of well-defined discrete macrocyclic hosts into ordered porous polymeric frameworks ( e.g., covalent organic frameworks, COFs) represents a promising strategy to transform many supramolecular chemistry concepts and principles well established in the solution phase into the solid state, which can enable a broad range of practical applications, such as high-efficiency molecular separation, heterogeneous catalysis, and pollution remediation. However, it is still a challenging task to construct macrocycle-embedded COFs. In this work, a novel pillar[5]arene-derived (P5 ) hetero-porous COF, denoted as P5-COF, was rationally designed and synthesized. Featuring the unique backbone structure, P5-COF exhibited selective adsorption of C2 H2 over C2 H4 and C2 H6, as well as significantly enhanced host–guest binding interaction with paraquat, in comparison with the pillar[5]arene-free COF analog, Model-COF . The present work established a new strategy for developing COFs with customizable molecular recognition/separation properties through the bottom-up "pre-porous macrocycle to porous framework" design.